Hydrodeoxygenation of guaiacol over Ni/carbon catalysts: effect of the support and Ni loading. Issue 4 (4th January 2016) - Dongil, A. B.; Ghampson, I. T.; García, R.; Fierro, J. L. G.; Escalona, N.
Abstract : Commercial carbon nanotubes (CNT), oxidized CNT (CNTox) and activated carbon (AC) were used as supports to prepare Ni/C catalysts with a nominal loading of 15 wt%. Abstract : Commercial carbon nanotubes (CNT), oxidized CNT (CNTox) and activated carbon (AC) were used as supports to prepare Ni/C catalysts with a nominal loading of 15 wt%. In addition, x Ni/CNT catalysts with loadings of x : 10, 12, 15, 17, 20 wt% were prepared. The catalysts were characterized by N2 physisorption, temperature-programmed decomposition (TPD), potentiometric titration, H2 -temperature programmed reduction (TPR), CO chemisorption and X-ray photoelectron spectroscopy (XPS). The catalysts were evaluated for the conversion of guaiacol at 573 K and 5 MPa H2 pressure for 4 h in a batch reactor. The activity of the x Ni/CNT catalysts was related to Ni dispersion, while their selectivity was similar and favored the formation of hydrogenation products. The activity of 15Ni/CNT catalyst was higher than those of 15Ni/CNTox and 15Ni/AC catalysts. The higher activity of the 15Ni/CNT catalyst compared to 15Ni/AC catalyst was possibly due to their different morphologies, while the lower activity of the 15Ni/CNTox catalyst was attributed to the limiting effect of surface oxygen groups on the support. In addition, the higher acidity of the 15Ni/CNTox catalyst enhanced its hydrogenolysis and deoxygenation capacities.